Emilie du châtelet between leibniz and newton - Hagengruber, Ruth (International Archives of the History of Ideas / Archives internationales d'histoire des idées,, 2012)
Emilie du Châtelet was one of the most influential woman philosophers of the Enlightenment. Her writings on natural philosophy, physics, and mechanics had a decisive impact on important scientific debates of the 18th century. Particularly, she took an innovative and outstanding position in the controversy between Newton and Leibniz, one of the fundamental scientific discourses of that time. The contributions in this volume focus on this "Leibnitian turn". They analyze the nature and motivation of Emilie du Châtelet's synthesis of Newtonian and Leibnitian philosophy. Apart from the Institutions Physiques they deal with Emilie du Châtelet's annotated translation of Isaac Newton's Principia. The chapters presented here collectively demonstrate that her work was an essential contribution to  the mediation between empiricist and rationalist positions in the history of science.